2023
DOI: 10.3389/fpls.2023.1089165
|View full text |Cite
|
Sign up to set email alerts
|

Plastome-based backbone phylogeny of East Asian Phedimus (Subgenus Aizoon: Crassulaceae), with special emphasis on Korean endemics

Abstract: Although the monophyly of Phedimus has been strongly demonstrated, the species relationships among approximately 20 species of Phedimus have been difficult to determine because of the uniformity of their floral characteristics and extreme variation of their vegetative characters, often accompanied by high polyploid and aneuploid series and diverse habitats. In this study, we assembled 15 complete chloroplast genomes of Phedimus species from East Asia and generated a plastome-based backbone phylogeny of the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 58 publications
(122 reference statements)
1
7
0
Order By: Relevance
“…Recently, Moon and Jang 25 reported that P. latiovalifolius, P. takesimensis , and P. middendorffianus should be recognized as distinct taxa based on their morphological characteristics. Molecular phylogenetic studies on interspecific relationships within the subgenus Aizoon species in Korea have encountered challenges in establishing robust phylogenetic relationships 26 , 27 . For instance, Seo et al (2020) 26 conducted a phylogenetic analysis of five Korean taxa ( P. takesimensis , P. aizoon , P. kamtschaticus , P. ellacombeanus , and P. latiovalifolius ) to assess the anagenetic speciation of P. takesimensis on Ulleung Island.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Moon and Jang 25 reported that P. latiovalifolius, P. takesimensis , and P. middendorffianus should be recognized as distinct taxa based on their morphological characteristics. Molecular phylogenetic studies on interspecific relationships within the subgenus Aizoon species in Korea have encountered challenges in establishing robust phylogenetic relationships 26 , 27 . For instance, Seo et al (2020) 26 conducted a phylogenetic analysis of five Korean taxa ( P. takesimensis , P. aizoon , P. kamtschaticus , P. ellacombeanus , and P. latiovalifolius ) to assess the anagenetic speciation of P. takesimensis on Ulleung Island.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overall lack of resolution and support, along with insufficient sampling, prevented the determination of the closest sister species to P. latiovalifolius . Recently, Kim et al (2023) 27 explored overall species relationships within the subgenus Aizoon using complete plastomes and nrDNA ITS sequences. Despite these efforts, neither the monophyly of P. latiovalifolius nor the phylogenetic relationships within Aizoon were adequately addressed, attributed to insufficient sampling and/or limited tree resolution and node support.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Phedimus is mainly distributed in Asia and Europe, with about 20 species [ 8 , 9 ]. P. takesimensis is narrowly restricted to Ulleung Island [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Phedimus is mainly distributed in Asia and Europe, with about 20 species [ 8 , 9 ]. P. takesimensis is narrowly restricted to Ulleung Island [ 8 ]. It has been suggested that the species is monophyletic with an ancestral species of continental origin [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation